Reading the rabbis: Christian Hebraism in the works of Herbert of Bosham - Visscher, Eva de (Commentaria, 2014)
In 'Reading the Rabbis' Eva De Visscher examines the Hebrew scholarship of Englishman Herbert of Bosham (c.1120-c.1194). Chiefly known as the loyal secretary and hagiographer of Archbishop Thomas Becket and enemy of Henry II, he appears here as an outstanding Hebraist whose linguistic proficiency and engagement with Rabbinic sources, including contemporary teachers, were unique for a northern-European Christian of his time. Two commentaries on the Psalms by Herbert form the focus of scrutiny. In demonstrating influence from Jewish and Christian texts such as Rashi, Hebrew-French glossaries, Hebrew-Latin Psalters, and Victorine scholarship, De Visscher situates Herbert within the context of an increased interest in the revision of Jerome's Latin Bible and literal exegesis, and a heightened Christian awareness of Jewish "other-ness"